The Magic of the Word - Klečková, Magdaléna (American & British Studies Annual, 2009)
The novels Ceremony, House made of Dawn and Love Medicine are chosen to demonstrate the function and importance of orality, myths, words and rituals. The investigation of storytelling tradition should be helpful to a meaningful analysis of how literature relates to the world. There is an attempt to draw a line between the Euramerican (”white”) and the Indian side, emphasizing the emotionality of the Indians and the comeback to old traditions. The ceremonies, stories and words are a demonstration of life and liveliness. Storytelling and song singing takes on the form of a ceremony, and brings relief and healing of soul.